Sub mucous cleft palate with fenestration - Shah, Sheerin (Medknow Publications & Media Pvt Ltd, 2014)
Congenital fenestration in sub mucous cleft palate is not a common identity. This patient is a 16-year-old female who presented with nasal speech. On examination, she had associated microform cleft lip with nasal deformity. Successful palatoplasty with intra velar veloplasty was done.